Studi distribusi tertangkapnya ikan pada Soma Tono selama satu siklus bulan - Octaviani Kaseti; Fanny Silooy; Johhny Budiman; Alfret Luasunaung; Lefrand Manoppo (JURNAL ILMU DAN TEKNOLOGI PERIKANAN TANGKAP, 2023)
This study aims to determine the distribution of caught fish in "soma tono" and the types of fish caught and how the fish are caught. Soma Tono is classified in gillnets that are rectangular in shape and equipped with buoys, upper ropes, lower ropes, weights and sign buoys. Operation of soma tono fishing gear consists of preparation, net lowering (setting), soaking (soaking) and lifting the net (hauling). The principle of soma tono fishing gear (gillnet) is to wait for fish to be entangled in the body of the net. The method used is a descriptive method, namely managing data obtained when making observations, interviews and documentation. The dominance of fish obtained by bounced fish, the type of fish obtained is the dominance of demersal fish or bottom fish, namely jackfruit seed fish (Upeneus molluccensin), lencam fish (Letrinus lencan), snapper fish (Lutjanus campechanus), lolosi fish (Caesio chrysozona), kuwe fish (Caranx ignobilis), grouper (Epinephelus longispinis), curisi fish (Nemipterus nemaptohorus), sako fish (Tylosurus crocodilus), parrotfish (Scarus rivulatus Valenciennes), puffer fish (Tetraodontidae), sardines (Amblygaster sirm),  baronang fish (Siganus) and sea eels (Muraenidae).  The results obtained four phases of the moon, namely the 1st  quarter moon phase (101.5 kg), the new moon phase (168.7 kg), 2nd quarter moon phase (89 kg) and the full moon  phase (63kg).